2011
DOI: 10.1308/003588411x588621
|View full text |Cite
|
Sign up to set email alerts
|

Early experience with laparoscopic extralevator abdominoperineal excision within an enhanced recovery setting: analysis of short-term outcomes and quality of life

Abstract: INTRODUCTION Conventional abdominoperineal excision for low rectal cancer has a higher local recurrence and reduced survival compared to anterior resection. An extralevator abdominoperineal excision (ELAPE) may improve outcome through removal of increased tissue in the distal rectum. Experience with ELAPE is limited and no studies have reported on quality of life (QOL) following this procedure. We describe a minimally invasive approach to ELAPE within an enhanced recovery programme, and present short-term resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 42 publications
3
20
0
Order By: Relevance
“…The results of the five studies which reported biological mesh repair are shown in Table 4. In a porcine mesh was used in four [19,20,26,27] and human mesh in one [17]. Data for each repair method were pooled.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the five studies which reported biological mesh repair are shown in Table 4. In a porcine mesh was used in four [19,20,26,27] and human mesh in one [17]. Data for each repair method were pooled.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the previous procedure named as ELAPE was mixed with cases that underwent "cylindrical APE". 15,16 The fat tissue of ischiorectal fossa might provide the support force and decrease the tension of the perineal wound. Our preliminary results showed that the ELAPE procedure, dissecting along the anatomic landmarks of outface of levator, could decrease the perineal would complication rate even by direct suture compared with conventional APE procedures.…”
Section: Discussionmentioning
confidence: 99%
“…23,31 the biological meshes consisted in 4 studies of crosslinked porcine meshes 23,26,27,39 and 1 study of non-crosslinked porcine meshes. 24,28,31,39 if only 2 studies were included in which all patients underwent neoadjuvant radiotherapy, perineal wound problems after eaPR occurred in a pooled percentage of 7.3% (95% Ci, 1.5-29.3; i 2 = 0%, χ 2 = 0.81; n = 20). 16,24 Perineal wound problems after eaPR and in at least 75% of the patients treated with radiotherapy occurred in a pooled percentage of 24.3% (95% Ci, 14.1-38.6; i 2 = 21%, χ 2 = 0.28; 4 studies, n = 78).…”
Section: Perineal Wound Problems and Perineal Hernia After Biologicalmentioning
confidence: 99%
“…28 in 1 study, both cross-linked and non-cross-linked meshes were used, 31 and, in 2 studies, human dermal meshes were used. 24,31 Perineal hernias after biological mesh closure following eaPR were reported in a pooled percentage of 8.2% (95% Ci, 4.8-13.6; i 2 = 0%, χ 2 = 0.45; 6 studies, n = 188). 24,28,31,39 if only 2 studies were included in which all patients underwent neoadjuvant radiotherapy, perineal wound problems after eaPR occurred in a pooled percentage of 7.3% (95% Ci, 1.5-29.3; i 2 = 0%, χ 2 = 0.81; n = 20).…”
Section: Perineal Wound Problems and Perineal Hernia After Biologicalmentioning
confidence: 99%